PATHOGENETIC ROLE OF ABZYME-TYPE AUTOANTIBODIES IN THE ORGAN-SPECIFIC AUTOIMMUNE PATHOLOGY - L. N. Luchverchyk (SPb RAACI, 2014)
Abstract. The work deals with quantitative methods developed for estimation of nuclease and proteolytic activities  of  autoantibodies.  By  means  of  these  techniques,  appropriate  catalytic  activities  of  abzyme-type antibodies were studied in patients with diabetes mellitus type 1, and in subjects with autoimmune thyroiditis. Oppositely directed changes of the mentioned catalytic activities have been found for autoantibodies of different specificity.  Autoantibodies  occurring  in  autoimmune  thyroiditis  showed  an  increase  of  both  nuclease  and proteolytic activities. Meanwhile, the autoantibodies in diabetes mellitus had increased nuclease activity, along with decreased proteolytic activity. These findings are suggestive for existence of two pathogenetic mechanisms in organ-specific autoimmune pathology that are associated either with direct involvement of Fab fragments of auto-antibodies in autoimmune destruction, or with complement-dependent lysis mediated by Fc-fragments and  cytotoxic  destruction  of  target  cells  by  cytotoxic T-lymphocytes.  The  unique  site-specific  catalytic autoantibodies  were  established  to  exert  a  selective destructive effect upon target cells, thus making a major contribution to the antibody-dependent mechanisms of cytotoxicity in autoimmune diseases. (Med. Immunol., 2011, vol. 13, N 2-3, pp 145-150)